Case report: Two cases of primary paratesticular liposarcoma - Li, Jiaxing; Wang, Jiayu; Han, Hu; Tian, Long; Yin, Hang (Frontiers in Oncology, 2022)
Paratesticular liposarcoma is a sporadic urological tumor. We report the clinical presentation, treatment course, and prognosis of 2 cases of primary paratesticular liposarcoma with different pathological types, with the aim of further understanding the diagnosis and treatment of this rare disease. Case 1 was a 53-years-old male patient who presented with left scrotal enlargement with swelling 3 years ago and was considered to have a testicular malignancy on preoperative CT scan and enhanced MRI. The patient underwent resection of the left scrotal mass and left orchiectomy under general anaesthesia. Histopathological study confirmed the diagnosis of dedifferentiated liposarcoma. At the 4-months follow-up, no local recurrence or distant metastasis was observed. Case 2 is a 42-years-old male patient with a left scrotal mass which was discovered six months ago. Preoperatively, he underwent CT plain and enhanced MRI examinations suggesting an intra-scrotal occupancy. The patient underwent scrotoscopic excision of the left scrotal mass under general anesthesia. Histopathological studies confirmed the diagnosis of highly differentiated liposarcoma. At the 10-months follow-up, no local recurrence or distant metastasis was observed. Preoperative differential diagnosis of paratesticular liposarcoma should be noted with testicular tumor and extra-abdominal hernia. Extensive local excision and, if necessary, concomitant radical testicular resection is the treatment of choice. If the tumor in the scrotum spreads to the inguinal region, surgical removal with the aid of a scrotoscope may be attempted. This procedure avoids the formation of a large incision in the inguinal region compared to traditional open surgery. Patients commonly experience local recurrence and less distant metastases after surgery, so long-term follow-up is recommended.